The strength of internal service quality on employee’s turnover intention and job satisfaction to organizational commitment - Ika Fuji Rahayu; Latipun Latipun (AMCA Journal of Community Development, 2021)
The purpose of this research is to examine the direct and indirect effects of internal service quality (ISQ) on turnover intention through job satisfaction and organizational commitment as mediating variables. There were 208 employees of Banks in Ternate, Indonesia, participating as the subjects of this research. In this research, Staying or Leaving Index, Job Descriptive Index, Organizational Commitment Scale and SERVQUAL are used to measure employee’s turnover intention, job satisfaction, organizational commitment, and ISQ, respectively. In the data analysis, a Path Process Micro Analysis was employed. The result of data analysis showed that ISQ has a direct effect on job satisfaction, organizational commitment, and turnover intention. Indirectly, ISQ also has an effect on turnover intention through job satisfaction and organizational commitment. Directly, the effect of ISQ on turnover intention is higher than indirect effect through mediating variables. The implication of this research results will be specially presented in the discussion.